The Concept Of Conflict In International Relations And Ways To Settle It - Rebwar Abdulrahim Abdullah; Azad Othman Salih (QALAAI ZANIST JOURNAL, 2020)
This research sheds light on the concept of conflict in international relations, in terms of its implications and importance in the literature on international relations, especially the school’s realist view of both classic and modern aspects of the international conflict, in addition to showing the extent of the impact of the conflict on international relations when referring to the conflict that occurred between States, and how they are settled. The phenomenon of conflict is historically one of the characteristics of international relations, and international relations are witnessing rapid changes that result in multiple tensions and diverging interests of countries. Although civilization and civilization are witnessing remarkable progress in all respects, and that international relations are based on firm foundations and pillars based on international laws and norms, the world is characterized by the multiplicity of regional and international conflicts and disputes resulting from different interests and aspirations in the midst of the imbalance in the regional balance of power and Internationalism, which is also the result of seeking to establish spheres of influence and control over the decision-making centers of weak and decaying states by the dominant super powers. Conflict management is one of the most important rules of the modern political game. It is considered an administrative and political art that requires political and administrative skills and fitness by decision makers and the bureaucratic apparatus that works with them, and therefore the study searches for those mechanisms that contribute to the conflict management process.